Partitioning of Space Among Trees in an Old-Growth Spruce Forest in Subarctic Fennoscandia - Pouta, Pasi; Kulha, Niko; Kuuluvainen, Timo; Aakala, Tuomas (Frontiers in Forests and Global Change, 2022)
The distribution of space among forest trees is linked to the availability of resources, among-tree competition, and hence forest dynamics. We studied partitioning of horizontal space among trees and related spatial structures in an old-growth Picea abies (L.) Karst -dominated forest in northeastern subarctic Fennoscandia, where Betula pubescens (Ehrh.) is an important co-dominant. Specifically, we asked (1) how does growing space occupied by trees vary by tree species and size in an old-growth forest with open canopy structure, and (2) at what scales does the variation in tree growing space occur? We mapped an 8.8 ha forest plot with 4,884 live trees. We used Voronoi polygons to quantify the horizontal space potentially available to each tree. We modeled the Voronoi polygon area as a function of tree size and species by using generalized additive models (GAM). We used i-to-any L-functions to study the scale-dependence of tree densities around focal trees, and mark correlation functions to study the relative sizes of trees close to each other. The GAM models showed that tree growing space increased non-linearly with tree size before saturating, and that overall growing space was larger for B. pubescens than for P. abies. Mean space occupied by trees roughly doubled from the smallest diameter class (0–5 cm) to the largest (>25 cm), from 13.7 to 26.7 m2. Depending on diameter class, shade-intolerant B. pubescens occupied on average 5–10 m2 more space than shade-tolerant P. abies. Trees close to each other were smaller than average. Size- and species-dependent differences in local tree densities accumulated mostly at the scale of a few meters but showed also broader-scale variation possibly related to edaphic variation within the study plot. The tree species- and size-related variation in the trees’ growing space suggests that among-tree competition, together with clustering of trees, shape the spatial assembly of the forest.